Induction Therapy for Kidney Transplant Recipients: Do We Still Need Anti‐IL2 Receptor Monoclonal Antibodies?. Issue 1 (5th July 2016) - Hellemans, R.; Bosmans, J.‐L.; Abramowicz, D.
Abstract : Induction therapy with antilymphocyte biological agents is widely used after kidney transplantation, most commonly T lymphocyte‐depleting rabbit‐derived antithymocyte globulin (rATG) or an IL‐2 receptor antagonist (IL2RA). Early randomized trials showed that rATG or IL2RA induction reduces early acute rejection, prompting recommendations by Kidney Disease Improving Global Outcomes that IL2RA induction be used routinely in first‐line therapy after kidney transplantation, with lymphocyte‐depleting induction reserved for high‐risk cases. These studies, however, mainly used outdated maintenance regimens. No large randomized trial has examined the effect of IL2RA or rATG induction versus no induction in patients receiving tacrolimus, mycophenolic acid and steroids. With this triple maintenance therapy, the addition of induction may achieve an absolute risk reduction for acute rejection of only 1–4% in standard‐risk patients without improving graft or patient survival. In contrast, rATG induction lowers the relative risk of acute rejection by almost 50% versus IL2RA in patients with high immunological risk. These recent data raise questions about the need for IL2RA in kidney transplantation, as it may no longer be beneficial in standard‐risk transplantation and may be inferior to rATG in high‐risk situations. Updated evidence‐based guidelines are necessary to support clinicians deciding whether and what induction therapy is required for their transplant patients today. Abstract : The authors discuss the role of induction therapy in contemporary kidney transplantation and question the need for interleukin‐2 receptor monoclonal antibodies.